How the teaching methods are applied in the Intermediate Intensive English II classes at the foreing language department of the University of El Salvador - Chinchilla Menjivar, Ana Jannette; Cruz Cruz, Roxana Lisset; Flores Alvarado, Delmy Ruth; Hernández Rivera, Ana Elizabeth; Herrera Martínez, Eliezer Antonio; Llanes, Jorge Homero; Salazar Murcia, Pedro Antonio (San Salvador : Universidad de El Salvador, 2004)
The methodology used in every class must be revised and classified according to the methods in which they are developed, this is what is shown in the presented essay which emphasizes in giving concept and some history about the methods, mentions his mentors, describes methods’ techniques, advantages and disadvantages of them. And as final point a proposal of an Eclectic Method which is recommended to achieve a good teaching-learning activity. The data has been collected from the Intermediate Intensive English II classes at the Foreign Language Department of the University of El Salvador. Moreover, different bibliography has been taken into account to get a variety of information, opinions, and thoughts about each method.
Tesis (Licenciatura en Idioma Inglés Opción Enseñanza)
Keywords: Métodos de enseñanza; Inglés -- Enseñanza